2014
DOI: 10.1016/j.econedurev.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating students’ evaluations of professors

Abstract: This paper contrasts measures of teacher effectiveness with the students' evaluations for the same teachers using administrative data from Bocconi University. The effectiveness measures are estimated by comparing the performance in follow-on coursework of students who are randomly assigned to teachers. We find that teacher quality matters substantially and that our measure of effectiveness is negatively correlated with the students' evaluations of professors. A simple theory rationalizes this result under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
140
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(164 citation statements)
references
References 48 publications
8
140
1
4
Order By: Relevance
“…In terms of rigor, students have been shown to reward faculty on end-of-semester course evaluations for awarding higher grades (Nimmer and Stone, 1991; Rodabaugh and Kravitz, 1994; Sailor et al ., 1997; Carrell and West, 2010). However, two studies that followed up on these same students in subsequent courses found a negative correlation between how they rated faculty and achievement in later courses (Carrell and West, 2010; Braga et al ., 2014), implying that students may be negatively rating the most rigorous, demanding, but yet effective instructors. Alternatively, it is possible that faculty do not provide critical feedback for fear of negative repercussions to the faculty being observed.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of rigor, students have been shown to reward faculty on end-of-semester course evaluations for awarding higher grades (Nimmer and Stone, 1991; Rodabaugh and Kravitz, 1994; Sailor et al ., 1997; Carrell and West, 2010). However, two studies that followed up on these same students in subsequent courses found a negative correlation between how they rated faculty and achievement in later courses (Carrell and West, 2010; Braga et al ., 2014), implying that students may be negatively rating the most rigorous, demanding, but yet effective instructors. Alternatively, it is possible that faculty do not provide critical feedback for fear of negative repercussions to the faculty being observed.…”
Section: Discussionmentioning
confidence: 99%
“…10 SETs should not be the only tool to assess teaching effectiveness, but should be combined with other methods of evaluations, including peer assessment and self-assessment. 2,6 The weight that SETs’ input carries in career decisions may be great and justifies the need to enhance their usefulness. 10,11,15 An administrative commitment to provide the appropriate human and monetary resources to support all aspects of faculty assessment is essential.…”
Section: Viewpoint 1: Formal Faculty Assessment Should Include Studenmentioning
confidence: 99%
“…20 In a third study, high SET ratings and student performance in a downstream related course were in fact negatively correlated. 2 …”
Section: Viewpoint 2: Student Evaluation Of Teaching Should Not Be Pamentioning
confidence: 99%
See 2 more Smart Citations